Analisis Faktor-Faktor Penentu Kualitas Kinerja Pegawai di Kantor Pencarian dan Pertolongan Kelas B Palu - Hamidah Dwiningtias; Taqwa Putra Budi Purnomo Sidi Hiram (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to identify the factors that shape employee performance quality and determine the most dominant factors. Data were collected through questionnaires distributed to 106 employees selected using a total sampling technique. The research instrument consisted of 40 indicators representing aspects of employee work, psychology, physical health, and lifestyle. Analysis was conducted using validity and reliability tests, the Kaiser-Meyer-Olkin (KMO) test, Bartlett's Test of Sphericity, Measure of Sampling Adequacy (MSA), factor extraction, and factor rotation. The results showed that of the 40 indicators analyzed, 37 met the criteria and formed eight main factors explaining 67.869% of the data variation. These factors include operational professionalism and work collaboration (29.791%), psychological work pressure (9.754%), compliance, accuracy, and work adaptation (7.668%), physical condition and daily activities (6.622%), healthy lifestyle habits (3.926%), rest, recovery, and self-control (3.779%), diet and nutritional awareness (3.348%), and work break duration (2.981%). Operational professionalism and work collaboration are the most dominant factors in shaping the quality of employee performance.